Combined Surgical Resection and Laser Interstitial Thermal Therapy for Glioblastoma: Technical Note - Vega, Rafael A.; Traylor, Jeffrey I.; Patel, Rajan; Muir, Matthew; Bastos, Dheigo C.A.; Prabhu, Sujit S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Glioblastoma multiforme (GBM) is an aggressive intracranial malignancy that confers a poor prognosis despite maximum surgical resection and chemoradiotherapy. Survival decreases further with deep-seated lesions. Laser interstitial thermal therapy (LITT) is an emerging minimally invasive technique for tumor ablation shown to reduce tumor burden effectively, particularly in deep-seated locations less amenable to gross total resection. We describe our initial technical experience of using the combination of LITT followed by surgical resection in patients with GBMs that exhibit both an easily accessible and deep-seated component.Materials and Methods Patients with GBM who received concurrent LITT and surgical resection at our institution were identified. Patient demographic and clinical information was procured from the University of Texas MD Anderson Cancer Center electronic medical record along with preoperative, postoperative, and 1-month follow-up magnetic resonance imaging (MRI).Results Four patients (n = 2 male, n = 2 female) with IDH-wild type GBM who received combined LITT and surgical resection were identified and analyzed retrospectively. All patients received chemoradiotherapy before presentation. All but one patient (75%) received resection before presentation. Median age was 54 years (range: 44–56 years). Median length of hospital stay was 6.5 days (range: 2–47 days). Median extent of combined ablation/resection was 90.4%. One of the four patients experienced complications in the perioperative or immediate follow-up periods. Local recurrence was observed in one patient during the follow-up period.Conclusion Malignant gliomas in deep-seated locations or in close proximity to white matter structures are challenging to manage. LITT followed by surgical resection may provide an alternative for tumor debulking that minimizes potential morbidities and extent of residual tumor. Further studies comparing this approach with standard resection techniques are warranted.
Keywords: laser interstitial thermal therapy; surgical resection; brain tumor; glioblastoma; deep-seated tumor